Livelihood dynamics and challenges to wellbeing in the drylands of rural East Africa – the Drylands Transform study population in the Karamoja border region - Schumann, Barbara; Turinawe, Alice; Lindvall, Kristina; Kyanjo, Joseph Lule; Kuule, Derick Ansyijar; Kawira, Caroline; Mwangi, Annrose; Mwangi, Peter; Hörnell, Agneta (Global health action, 2025)
The Karamoja region in the East African drylands is a rural, impoverished setting where pastoralism is increasingly replaced by other livelihood strategies. Understanding the socioeconomic contexts as well as their local variations is key for sustainable development of communities. The aim of the present paper is to describe the baseline survey of the Drylands Transform project, its setting, methods and key findings. In June 2022, a survey was conducted with 944 randomly selected households at four study sites in the Karamoja border region of Kenya and Uganda. Data were analyzed using descriptive statistics. Main livelihood forms were pastoralism and agropastoralism, while many households also relied on other sources of income. At some study sites, livestock keeping was abandoned by many residents due to cattle raiding and droughts. Only 4% of households were rated as food secure. The proportion of malnutrition among children aged 6-59 months varied across sites between 3% and 17% and was considerably higher among women. Climate change, water shortage, social conflicts and marginalization pose barriers to food security and wellbeing for rural populations in the East African drylands. There are, however, opportunities for development through income diversification, the improvement of land health, the promotion of kitchen gardens and other measures of sustainable agriculture.